Insiders and outsiders : paradise and reality in Mallorca - Waldren, Jacqueline, 1937- (New directions in anthropology, 1996)
"The indigenous population of Deia has lived side by side with increasing numbers of foreigners over the past century. What has occurred there over this period offers an example of how the population of one Mediterranean village has gained full advantage from the economic opportunities opened up by foreign investments, without losing the fabric of social relations, the meaning and values of their culture. Deia has been able to continue as a community with its own symbolic boundaries and identity, not in spite of the outsiders (some of whom were well-known literary personalities, artists and musicians) but because of their presence. This study shows how, under the impact of wars, migration, national politics, global economic and technological developments and especially tourism, the categories of Insider and Outsider are contracted and expanded, and reinterpreted to fit the constantly changing 'reality' of the society, assuming different meanings at different times. The conflicts and resulting compromises over a hundred-year period have provided a sense of history that allows each group to define, develop, adapt and sustain their sense of belonging to their own community."--Jacket